High bonding strength flame-retardant composite foam board and preparation method thereof

By combining modified epoxy resin with foaming agent, high bonding strength flame-retardant composite foam board is prepared, which solves the problems of harmful solvent use and highly toxic gas release during combustion in the preparation process of traditional foam board, and achieves environmentally friendly and efficient thermal insulation and noise reduction performance, which is suitable for application in multiple fields.

CN119858374BActive Publication Date: 2025-10-10NANJING NUOBANG NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510074140.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-10-10
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

Existing foam boards use harmful solvents during the preparation process, release highly toxic gases when burned, and have insufficient thermal and sound insulation properties. Traditional sandwich panels have complex structures and poor bonding strength.

Method used

Epoxy foam-based composite materials are used. By combining modified epoxy resin with foaming agent, flame retardant, etc., a high bonding strength flame-retardant composite foam board with a sandwich structure is formed. No adhesive is required to bond the outer skin and inner skin to the epoxy foam core. The closed-cell structure of the epoxy foam is used to prevent heat radiation and sound conduction.

Benefits of technology

It achieves high bonding strength, environmentally friendly heat insulation and noise reduction performance, is suitable for the manufacture of high-strength composite materials, and is widely used in naval vessels, military aircraft, aircraft and construction fields, with excellent flame retardancy and sound insulation and heat insulation effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119858374B_ABST
    Figure CN119858374B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of materials, in particular to a high-bonding-strength flame-retardant composite foam board and a preparation method thereof, wherein the epoxy foam material core has a plurality of closed-cell small bubbles inside, effectively preventing the heat radiation effect and the sound conduction of the epoxy foam sandwich board, achieving the effect of heat insulation and noise reduction, and the heat insulation and noise reduction performance is better than that of the honeycomb sandwich board; in addition, the environmentally-friendly flame-retardant epoxy foaming mixture used for preparing the epoxy foam base sandwich board has good adhesion with the inner and outer skins, does not need to use adhesive for bonding, does not need to add harmful solvents, the epoxy foaming mixture is cast between the inner and outer skins, a sandwich-shaped whole is formed through a one-time foaming and curing process, and the appearance shape of the composite is not limited, the epoxy foam sandwich board has simple structure, easy forming, good sandwich-shaped whole structure rigidity, good heat insulation and noise reduction performance, excellent environmental protection performance, can be applied to the manufacturing of high-strength composites, and has wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials, and in particular to a high-bonding-strength flame-retardant composite foam board and a preparation method thereof. Background Art

[0002] In the existing material field, foam boards are commonly used as thermal insulation, sound insulation and filling materials, and have a wide range of application scenarios. Traditional foam boards, such as polyurethane foam boards, have certain thermal insulation and sound insulation properties, but they have many defects. On the one hand, the preparation process of polyurethane foam often relies on chlorofluorocarbon (CFC) foaming agents, which cause great damage to the atmospheric ozone layer. At the same time, a large amount of organic solvents and additives are required during the preparation. Over time, volatile organic small molecules such as benzene and toluene in the foam continue to evaporate, causing serious harm to the environment and human health. Moreover, in the event of a fire, polyurethane rigid foam is extremely easy to ignite, and the combustion process releases a large amount of highly toxic gases such as hydrogen cyanide, carbon monoxide and nitric oxide. When the concentration reaches 400ppm, it can cause poisoning and death, posing a huge safety hazard.

[0003] In addition, the common sandwich panel structure is composed of a sandwich layer and inner and outer skins, the inner and outer skins are bonded to the two sides of the sandwich layer by adhesives, the sandwich layer is a honeycomb core layer or a foam core layer, the honeycomb core layer is a paper honeycomb core, an aluminum honeycomb core or a plastic honeycomb core, and the foam core layer is a foam material such as polyurethane (PU) foam, phenolic foam and polystyrene foam (EPS). The sandwich layer is a honeycomb core layer, which is called a honeycomb sandwich panel, and the sandwich layer is a foam core layer, which is called a foam sandwich panel. Although the honeycomb sandwich panel structure has the advantages of good rigidity, high load ratio and less material use, due to the convection and heat radiation of the air in the honeycomb cell between the inner and outer skins, the thermal insulation performance is poor.

[0004] Patent document CN103291035A discloses a honeycomb sandwich panel. The invention bonds honeycomb aluminum and glass fiber cloth together through an adhesive to form a honeycomb sandwich panel: the upper and lower skins are both bonded and fixed by an adhesive layer and a honeycomb core. However, the sandwich panel core material and the panel provided by this method are prone to peeling, which affects the mechanical properties. For example, patent document CN201510108674 discloses a honeycomb aluminum-epoxy resin composite sandwich panel and its preparation method. The sandwich panel is a five-layer structure sandwich panel, including a pure epoxy resin protective surface layer, an epoxy resin / honeycomb aluminum composite layer, a honeycomb aluminum core layer, an epoxy resin / honeycomb aluminum composite layer and a pure epoxy resin protective surface layer. Although the sandwich panel provided by the invention has good rigidity, the sandwich panel structure has many layers, the manufacturing process is complex, the cycle is also very long, and the bonding method between the skin and the sandwich layer is not explained. In addition, patent document CN102198744A discloses a method for manufacturing a phenolic foam-filled honeycomb core reinforced advanced composite material, which is characterized by using an open-cell phenolic impregnated honeycomb as a substrate, filling the open-cell position of the substrate with a foamed phenolic resin and foaming it to form a phenolic foam-filled honeycomb core material, and then compounding the core material with a phenolic fiber-reinforced surface material to form a phenolic foam-filled honeycomb core reinforced advanced composite material. This advanced composite material is light in weight, heat-insulating, sound-insulating, flame-retardant, and has strong corrosion resistance. It can be widely used in fields such as aviation, ships, and rail transportation facilities manufacturing. However, the sandwich panel structure manufactured by this method has many layers, the molding process is complex, the cost is high, and the foam expansion causes the honeycomb grid to deform and crack, which destroys the strength of the honeycomb core.

[0005] Therefore, in view of the above-mentioned related technologies, it is urgent to develop a high-bonding strength flame-retardant composite foam board and a preparation method thereof. Summary of the Invention

[0006] In view of this, the purpose of the present invention is to provide a high bonding strength flame retardant composite foam board and a preparation method thereof, so as to provide an epoxy foam-based sandwich panel that is easy to form, has high rigidity, and has good thermal insulation and sound insulation properties.

[0007] Based on the above objectives, the present invention provides a high-bonding-strength flame-retardant composite foam board and a preparation method thereof.

[0008] A high-bonding-strength flame-retardant composite foam board, comprising, from top to bottom, an outer skin, an epoxy foam core, and an inner skin;

[0009] The epoxy foam core is an epoxy foam-based composite material;

[0010] The epoxy foam-based composite material is prepared from the following raw materials: epoxy resin base material, curing agent, foaming agent, flame retardant, surfactant and toughening agent;

[0011] The epoxy resin base material is obtained by mixing bisphenol A epoxy resin and modified epoxy resin;

[0012] The modified epoxy resin is rubber-modified bisphenol A epoxy resin.

[0013] Preferably, the mass ratio of the epoxy resin base material, the curing agent, the foaming agent, the flame retardant, the surfactant and the toughening agent in the epoxy foam-based composite material is 125-128:13-15:11-14:48-52:1-1.5:10-10.5.

[0014] Preferably, the mass ratio of bisphenol A epoxy resin to modified epoxy resin in the epoxy resin base material is 100-105:11.5-15.

[0015] Preferably, the curing agent is diethylenetriamine;

[0016] The foaming agent is pentane;

[0017] The flame retardant is aluminum hydroxide;

[0018] The surfactant is silicone oil;

[0019] The toughening agent is nitrile rubber.

[0020] Preferably, the thickness of the outer skin is 0.15-10 mm, and the outer skin is any one of aluminum alloy, steel plate, PC, ABS, PA66, PVC, glass fiber, glass fiber reinforced plastic and carbon fiber.

[0021] Preferably, the thickness of the inner skin is 0.15-10 mm, and the inner skin is any one of aluminum alloy, steel plate, PC, ABS, PA66, PVC, glass fiber, glass fiber reinforced plastic and carbon fiber.

[0022] Preferably, the epoxy foam core has a thickness of 3-100 mm.

[0023] Preferably, the preparation process of the modified epoxy resin is as follows:

[0024] Step A1. A bisphenol A epoxy resin is placed in a three-necked flask equipped with a stirrer and a thermometer and preheated at 80°C for 10-15 minutes to reduce the viscosity of the bisphenol A epoxy resin and facilitate subsequent mixing. Carboxyl-terminated nitrile rubber is then added to the bisphenol A epoxy resin and stirred at 90°C for 3 hours at a stirring speed of 300-500 rpm to allow the carboxyl groups in the carboxyl-terminated nitrile rubber to fully react with the epoxy groups in the epoxy resin to obtain a pre-modified epoxy resin.

[0025] Step A2. Add styrene-butadiene rubber particles to the pre-modified epoxy resin and mix them at room temperature using a high-speed stirrer at a stirring speed of 1000-1200 rpm for 30-40 minutes to ensure that the solid rubber particles are evenly dispersed in the modified epoxy resin to obtain a modified epoxy resin.

[0026] Preferably, the mass ratio of the carboxyl-terminated nitrile rubber to the bisphenol A epoxy resin in step A1 is 12-16:90-110.

[0027] Preferably, the mass ratio of the styrene-butadiene rubber particles to the pre-modified epoxy resin in step A2 is 10-13:110-120.

[0028] A method for preparing a high-bonding-strength flame-retardant composite foam board comprises the following steps:

[0029] Step S1. Preheat the bisphenol A epoxy resin and the modified epoxy resin at 35-40°C, add the flame retardant, and stir at 45-50°C for 15 minutes at a stirring speed of 500-800 rpm. Then, add the foaming agent and stir at 800-1000 rpm for 8 minutes to obtain a mixture 1;

[0030] Step S2. Adding a surfactant and a toughening agent to the mixture 1, stirring at 400-700 rpm for 12 min, and finally adding a curing agent, stirring at 800-1200 rpm for 3 min to obtain an epoxy foam-based composite material;

[0031] Step S3. Place the inner and outer skins of the same height vertically against the mold wall in the mold and secure them. The mold height should be consistent with the inner and outer skins, and the bottom of the mold should be in close contact with the inner and outer skins.

[0032] Step S4. Inject the epoxy foam-based composite material into a mold, place it at room temperature for 6-24 hours, then place it at 80-120°C for 2-3 hours, and demold it after foaming and curing to obtain a high-bonding-strength flame-retardant composite foam board.

[0033] Beneficial effects of the present invention:

[0034] The present invention provides a high-bonding-strength flame-retardant composite foam board and a preparation method thereof, wherein the epoxy foam-based sandwich panel integrates filling, potting, and bonding processes. Since there are many closed-cell small bubbles inside the epoxy foam material core, the heat radiation effect and sound conduction of the epoxy foam sandwich panel are effectively prevented, thereby achieving the effect of heat insulation and noise reduction. Compared with honeycomb sandwich panels, the heat insulation and noise reduction performance are better. In addition, the environmentally friendly flame-retardant epoxy foaming mixture used in the preparation of the epoxy foam-based sandwich panel has good adhesion to the inner and outer skins, without the need for adhesive bonding or the addition of harmful solvents. The epoxy foam-based sandwich panel is formed by casting the epoxy foam mixture between the inner and outer skins and undergoing a single foaming and curing process to form a sandwich-shaped whole. The epoxy foam-based sandwich panel is also not limited to the appearance of the composite.

[0035] Epoxy foam sandwich panels offer a simple structure, easy molding, and excellent overall structural strength, along with superior thermal insulation and noise reduction, along with superior environmental performance. They are suitable for the manufacture of high-strength composite materials. Epoxy foam composites not only effectively enhance structural wall strength but also absorb impact load energy, enhancing the structure's resistance to impact damage. They hold broad application prospects in naval vessels, military aircraft, buildings, and offshore structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0037] Figure 1 Schematic diagram of the structure of the epoxy foam core in the present invention;

[0038] Figure 2 Schematic diagram of the structure of the honeycomb sandwich panel in Comparative Example 1 and Comparative Example 2 of the present invention;

[0039] Figure 3 This is a schematic structural diagram of the epoxy foam sandwich panel in Example 1 of the present invention;

[0040] Figure 4 This is a schematic structural diagram of the epoxy foam sandwich panel in Example 2 of the present invention;

[0041] Figure 5 This is a schematic structural diagram of the epoxy foam sandwich panel in Example 3 of the present invention;

[0042] Figure 6 This is a schematic structural diagram of the epoxy foam sandwich panel in Example 4 of the present invention;

[0043] Figure 7This is a schematic structural diagram of the epoxy foam sandwich panel in Example 5 of the present invention;

[0044] Figure 8 This is a schematic structural diagram of the epoxy foam sandwich panel in Example 6 of the present invention;

[0045] Figure 9 This is a schematic structural diagram of the epoxy foam sandwich panel in Example 7 of the present invention;

[0046] Figure 10 This is a schematic structural diagram of the epoxy foam sandwich panel in Example 8 of the present invention;

[0047] Figure 11 This is a schematic structural diagram of the epoxy foam sandwich panel in Example 9 of the present invention;

[0048] Figure 12 Schematic diagram of the structure of the epoxy foam sandwich panel in Example 10 of the present invention;

[0049] Figure 13 The heat and sound insulation performance test results of the samples in Example 1 and Comparative Example 1 of the present invention are as follows;

[0050] Figure 14 The test results of thermal insulation and sound insulation performance of the samples in Example 2 and Comparative Example 2 of the present invention are as follows;

[0051] Figure 15 These are the sound pressure intensity test results of the samples in Examples 1-2 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION

[0052] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to specific embodiments.

[0053] Example 1:

[0054] Depend on Figure 3 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an epoxy foam core and an inner skin;

[0055] The thickness of the outer skin is 1.5mm, and the outer skin is made of aluminum alloy;

[0056] The thickness of the epoxy foam core is 30mm;

[0057] The thickness of the inner skin is 1.5m and the inner skin is made of aluminum alloy.

[0058] Example 2:

[0059] Depend on Figure 4 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an epoxy foam core and an inner skin;

[0060] The thickness of the outer skin is 1.5mm, and the outer skin is a steel plate;

[0061] The thickness of the epoxy foam core is 30mm;

[0062] The thickness of the inner skin is 1.5mm and the inner skin is a steel plate.

[0063] Example 3:

[0064] Depend on Figure 5 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an epoxy foam core and an inner skin;

[0065] The thickness of the outer skin is 2mm, and the outer skin is made of aluminum alloy;

[0066] The thickness of the epoxy foam core is 10mm;

[0067] The thickness of the inner skin is 0.15mm and the inner skin is a steel plate;

[0068] Example 4:

[0069] Depend on Figure 6 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an epoxy foam core and an inner skin;

[0070] The thickness of the outer skin is 2mm, and the outer skin is made of PA66 material;

[0071] The thickness of the epoxy foam core is 50mm;

[0072] The thickness of the inner skin is 2mm and the inner skin is made of PA66 material.

[0073] Example 5:

[0074] Depend on Figure 7 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an epoxy foam core and an inner skin;

[0075] The thickness of the outer skin is 3mm, and the outer skin is made of ABS material;

[0076] The thickness of the epoxy foam core is 40mm;

[0077] The thickness of the inner skin is 3mm and the inner skin is made of ABS material.

[0078] Example 6:

[0079] Depend on Figure 8 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an epoxy foam core and an inner skin;

[0080] The thickness of the outer skin is 2mm, and the outer skin is made of PA66 material;

[0081] The thickness of the epoxy foam core is 30mm;

[0082] The thickness of the inner skin is 2mm and the inner skin is made of ABS material.

[0083] Example 7:

[0084] Depend on Figure 9 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an epoxy foam core and an inner skin;

[0085] The thickness of the outer skin is 2mm, and the outer skin is made of aluminum alloy;

[0086] The thickness of the epoxy foam core is 40mm;

[0087] The thickness of the inner skin is 3mm and the inner skin is made of PA66 material.

[0088] Example 8:

[0089] Depend on Figure 10 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an epoxy foam core and an inner skin;

[0090] The thickness of the outer skin is 0.2mm, and the outer skin is a carbon fiber plate;

[0091] The thickness of the epoxy foam core is 90mm;

[0092] The thickness of the inner skin is 1mm, and the inner skin is a carbon fiber plate.

[0093] Example 9:

[0094] Depend on Figure 11 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an epoxy foam core and an inner skin;

[0095] The thickness of the outer skin is 2mm and the outer skin is steel plate;

[0096] The thickness of the epoxy foam core is 100mm;

[0097] The thickness of the inner skin is 0.2mm and the inner skin is glass fiber cloth.

[0098] Example 10:

[0099] Depend on Figure 12 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an epoxy foam core and an inner skin;

[0100] The thickness of the outer skin is 2mm, and the outer skin is made of PA66 material;

[0101] The thickness of the epoxy foam core is 50mm;

[0102] The thickness of the inner skin is 5mm, and the inner skin is a fiberglass plate.

[0103] Example 11: A method for preparing a modified epoxy resin, comprising the following steps:

[0104] S1. 90 g of bisphenol A epoxy resin was placed in a three-necked flask equipped with a stirrer and a thermometer and preheated at 80°C for 10 min to reduce the viscosity of the bisphenol A epoxy resin and facilitate subsequent mixing. 12 g of carboxyl-terminated nitrile rubber was then added to the bisphenol A epoxy resin and stirred at 90°C for 3 h at 300 rpm to allow the carboxyl groups in the carboxyl-terminated nitrile rubber to fully react with the epoxy groups in the epoxy resin to obtain a pre-modified epoxy resin.

[0105] S2. Add 10 g of styrene-butadiene rubber particles to 110 g of pre-modified epoxy resin and mix them at room temperature using a high-speed stirrer at a stirring speed of 1000 rpm for 30 min to ensure that the solid rubber particles are evenly dispersed in the modified epoxy resin to obtain a modified epoxy resin.

[0106] Example 12: A method for preparing a modified epoxy resin, comprising the following steps:

[0107] S1. 100 g of bisphenol A epoxy resin was placed in a three-necked flask equipped with a stirrer and a thermometer and preheated at 80°C for 12 min to reduce the viscosity of the bisphenol A epoxy resin and facilitate subsequent mixing. 14 g of carboxyl-terminated nitrile rubber was then added to the bisphenol A epoxy resin and stirred at 90°C for 3 h at 400 rpm to allow the carboxyl groups in the carboxyl-terminated nitrile rubber to fully react with the epoxy groups in the epoxy resin to obtain a pre-modified epoxy resin.

[0108] S2. Add 12 g of styrene-butadiene rubber particles to 115 g of pre-modified epoxy resin and mix them at room temperature using a high-speed stirrer at a stirring speed of 1100 rpm for 35 min to ensure that the solid rubber particles are evenly dispersed in the modified epoxy resin to obtain a modified epoxy resin.

[0109] Example 13: A method for preparing a modified epoxy resin, comprising the following steps:

[0110] S1. 110 g of bisphenol A epoxy resin was placed in a three-necked flask equipped with a stirrer and a thermometer and preheated at 80°C for 15 min to reduce the viscosity of the bisphenol A epoxy resin and facilitate subsequent mixing. 16 g of carboxyl-terminated nitrile rubber was then added to the bisphenol A epoxy resin and stirred at 90°C for 3 h at a stirring speed of 500 rpm to allow the carboxyl groups in the carboxyl-terminated nitrile rubber to fully react with the epoxy groups in the epoxy resin to obtain a pre-modified epoxy resin.

[0111] S2. Add 13 g of styrene-butadiene rubber particles to 120 g of pre-modified epoxy resin and mix them at room temperature using a high-speed stirrer at a stirring speed of 1200 rpm for 40 min to ensure that the solid rubber particles are evenly dispersed in the modified epoxy resin to obtain a modified epoxy resin.

[0112] Example 14: A method for preparing a high-bonding-strength flame-retardant composite foam board, comprising the following steps:

[0113] S1. 100 g of bisphenol A epoxy resin and 11.5 g of the modified epoxy resin prepared in Example 11 were preheated at 35 ° C, 48 g of aluminum hydroxide was added, and stirred at 45 ° C for 15 min at a stirring speed of 500 rpm, and then 11 g of pentane was added and stirred at 800 rpm for 8 min to obtain a mixture 1;

[0114] S2 was added to the mixture 1g silicone oil and 10g nitrile rubber, stirred at 400rpm for 12min, and finally added 13g diethylenetriamine, stirred at 800rpm for 3min to obtain an epoxy foam-based composite material;

[0115] S3. The inner and outer skins of the same height are placed vertically against the mold wall in the mold and fixed. The mold height is consistent with the inner and outer skins, and the bottom of the mold is in close contact with the inner and outer skins.

[0116] S4. The epoxy foam-based composite material is injected into a mold, first placed at room temperature for 8 hours, and then placed at 120°C for 1 hour. After foaming and curing, the mold is demolded to obtain a high-bonding strength flame-retardant composite foam board. The expansion ratio of the epoxy foam mixture after foaming and curing is 500%.

[0117] Example 15: A method for preparing a high-bonding-strength flame-retardant composite foam board, comprising the following steps:

[0118] S1. 103 g of bisphenol A epoxy resin and 13 g of the modified epoxy resin prepared in Example 12 were preheated at 37 ° C, 50 g of aluminum hydroxide was added, and the mixture was stirred at 47 ° C for 15 min at a stirring speed of 650 rpm, and then 12 g of pentane was added and stirred at 900 rpm for 8 min to obtain a mixture 1;

[0119] S2 was added to the mixture 1.3g silicone oil and 10.3g nitrile rubber, stirred at 550rpm for 12min, and finally added 14g diethylenetriamine, stirred at 1000rpm for 3min to obtain an epoxy foam-based composite material;

[0120] S3. The inner and outer skins of the same height are placed vertically against the mold wall in the mold and fixed. The mold height is consistent with the inner and outer skins, and the bottom of the mold is in close contact with the inner and outer skins.

[0121] S4. The epoxy foam-based composite material is injected into a mold, first placed at room temperature for 24 hours, and then placed at 80°C for 3 hours. After foaming and curing, the mold is demoulded to obtain a high-bonding strength flame-retardant composite foam board. The expansion ratio of the epoxy foam mixture after foaming and curing is 500%.

[0122] Example 16: A method for preparing a high-bonding-strength flame-retardant composite foam board, comprising the following steps:

[0123] S1. 105g of bisphenol A epoxy resin and 15g of the modified epoxy resin prepared in Example 13 were preheated at 40 ° C, 52g of aluminum hydroxide was added, and stirred at 800 rpm for 15min at 50 ° C, and then 14g of pentane was added and stirred at 1000 rpm for 8min to obtain a mixture 1;

[0124] S2 was added to the mixture 1.5g silicone oil and 10.5g nitrile rubber, stirred at 700rpm for 12min, and finally added 15g diethylenetriamine, stirred at 1200rpm for 3min to obtain an epoxy foam-based composite material;

[0125] S3. The inner and outer skins of the same height are placed vertically against the mold wall in the mold and fixed. The mold height is consistent with the inner and outer skins, and the bottom of the mold is in close contact with the inner and outer skins.

[0126] S4. The epoxy foam-based composite material is injected into a mold, first placed at room temperature for 16 hours, and then placed at 100°C for 2 hours. After foaming and curing, the mold is demolded to obtain a high-bonding strength flame-retardant composite foam board. The expansion ratio of the epoxy foam mixture after foaming and curing is 350%.

[0127] Comparative Example 1:

[0128] Depend on Figure 2 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an adhesive layer, a honeycomb core, an adhesive layer and an inner skin;

[0129] The thickness of the outer skin is 1.5mm, and the outer skin is made of aluminum alloy;

[0130] The thickness of the inner skin is 1.5mm, and the inner skin is made of aluminum alloy;

[0131] The height of the honeycomb core is 30 mm, and the honeycomb core is an aluminum honeycomb.

[0132] Comparative Example 2:

[0133] Depend on Figure 2 As shown, a high bonding strength flame retardant composite foam board comprises, from the outside to the inside, an outer skin, an adhesive layer, a honeycomb core, an adhesive layer and an inner skin;

[0134] The thickness of the outer skin is 1.5mm, and the outer skin is a steel plate;

[0135] The thickness of the inner skin is 1.5mm and the inner skin is a steel plate;

[0136] The height of the honeycomb core is 30 mm, and the honeycomb core is an aluminum honeycomb.

[0137] from Figure 13-14 It can be seen that the faster the temperature rises and the closer the stable temperature is to the heat source temperature, the better the thermal conductivity and the worse the thermal insulation performance. According to the final stable temperature and the speed of temperature rise, it can be judged that: thermal conductivity: comparative example 1> comparative example 2> embodiment 2> embodiment 1; thermal insulation performance: embodiment 1> embodiment 2 is greater than comparative example 2> comparative example 1, indicating that the epoxy foam-based sandwich panel has better thermal insulation performance. Figure 15 It can be seen from the sound pressure intensity test results of the samples that when the sound is between 500-2000Hz, the Pq value of the sample in Example 1 is the smallest, and the Pq value of Comparative Example 1 is the largest. According to the analysis of the sound insulation performance test principle, the smaller the Pq value, the greater the sound insulation coefficient. Therefore, the thermal insulation performance can be judged: Example 1> Example 2 is greater than Comparative Example 2> Comparative Example 1, indicating that the epoxy foam-based sandwich panel has better sound insulation performance.

[0138] The high-bonding strength flame-retardant composite foam board of the present invention uses a high-performance flame-retardant epoxy resin as the core sandwich layer material, with an outer layer as the outer skin and an inner layer as the inner skin. The outer skin and inner skin can be selected from one or more metal materials such as aluminum alloy and steel plate, plastic materials such as PC, ABS, PA66, PI, PEEK and PVC, and composite materials such as glass fiber, fiberglass reinforced plastic and carbon fiber board. By combining different materials, it can meet diverse usage requirements and adapt to different working conditions. The composite foam board is epoxy foam-based and has a bulk density of 0.15-1.00g / cm 3, composite materials with excellent flame retardant properties, will not produce highly toxic gas hydrogen cyanide during combustion, can be safely used in crowded places, effectively protecting the lives of people. And after testing, in the sound frequency range of 315-2000Hz, this composite foam board shows good sound insulation performance, which can effectively block external noise interference; under the same heat source, compared with honeycomb sandwich panels, its temperature is 10-25℃ lower, with excellent thermal insulation performance, which can greatly reduce heat transfer. In addition, no harmful gases and volatile harmful solvents are produced throughout the preparation process. Even if exposed to high temperature and open flame conditions, no toxic gases will be released. The environmental protection performance is outstanding, which is in line with the current green development concept. After the epoxy foaming mixture undergoes the foaming and curing process, its expansion ratio can reach 130%-500%, ensuring that the foam core layer forms an ideal closed-cell structure, giving the composite foam board excellent performance.

[0139] Comparative Example 3:

[0140] Compared with Example 14, this comparative example did not add modified epoxy resin during the preparation process of the high bonding strength flame-retardant composite foam board. The remaining steps and parameters were the same and will not be repeated in this comparative example. Finally, a high bonding strength flame-retardant composite foam board was obtained.

[0141] Comparative Example 4:

[0142] Compared with Example 14, this comparative example only replaces the "modified epoxy resin" with the "pre-modified epoxy resin", and the remaining steps and parameters are the same. This comparative example will not be repeated, and finally a high bonding strength flame-retardant composite foam board is obtained.

[0143] Comparative Example 5:

[0144] Compared with Example 14, this comparative example only replaces the "modified epoxy resin prepared in Example 11" with "a mixture of equal amounts of end-carboxyl nitrile rubber, bisphenol A epoxy resin and styrene-butadiene rubber". The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a high-bonding strength flame-retardant composite foam board is obtained.

[0145] Comparative Example 6:

[0146] Compared with Example 14, this comparative example only adjusts the amount of "bisphenol A epoxy resin" from "100g" to "11.5g", and adjusts the amount of "modified epoxy resin prepared in Example 11" from "11.5g" to "100g". The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a high-bonding-strength flame-retardant composite foam board is obtained.

[0147] Performance tests: The following performance tests were performed on the samples prepared in Examples 14 to 16 and Comparative Examples 3 to 6. For Examples 14 to 16 and Comparative Examples 3 to 6, at least five samples of the same specifications were prepared for each performance test to ensure the accuracy and reliability of the data:

[0148] Bond strength test: Refer to ASTM D1002-10 standard and use a universal material testing machine for testing. Cut the prepared composite foam board into specimens of specified size. The bonding surface between the outer skin of the specimen and the epoxy foam core must be flat. Use adhesive to bond the outer skin at one end of the specimen to another board of the same material, ensuring that the bond is firm and free of bubbles. Stretch the specimen at a tensile rate of 5mm / min until the outer skin and the foam core are peeled off. Record the maximum tensile force displayed by the testing machine at this time. Calculate the bond strength based on the bonding area of ​​the specimen in MPa. Before conducting the bond strength test, the specimen must be visually inspected to ensure that the bonding surface is free of defects, impurities, and other factors that may affect the test results. When installing the specimen on the universal material testing machine, ensure that the specimen is evenly stressed and the stretching direction is perpendicular to the bonding surface.

[0149] Flame retardant performance test: A vertical combustion test is conducted in accordance with the UL94 standard. A sample with a size of 125mm × 13mm × thickness (the actual thickness of the composite foam board) is fixed vertically in a combustion device. The bottom of the sample is ignited with a specified flame (methane flame, flame height approximately 20mm). After burning for 10 seconds, the flame is removed and the burning time of the sample, the presence of dripping matter, and the self-extinguishing time after the flame is extinguished are recorded. Flame retardant grades are assessed according to the standard and are divided into V-0, V-1, V-2, etc. V-0 is the highest flame retardant grade, indicating that the total burning time of the sample does not exceed 10 seconds after two applications of flame, and there are no dripping matter that ignites the absorbent cotton. The flame retardant performance test must be conducted in a well-ventilated environment to ensure the safety of the test personnel. After each sample test is completed, the combustion device must be cooled to room temperature before testing the next sample to avoid the influence of temperature on the test results.

[0150] Thermal insulation performance test: According to ASTM C518 standard, use the heat flow meter method. Install the composite foam board sample between the hot and cold plates of the heat flow meter device. The cold plate temperature is set to 25℃ and the hot plate temperature is set to 70℃. After the temperature stabilizes, measure the heat flux density (W / m 2 ) and calculate thermal conductivity (W / m·K) based on the thickness of the specimen. The lower the thermal conductivity, the better the insulation performance. During the insulation performance test, pay close attention to the temperature stability of the heat flow meter device to ensure that the temperature fluctuations of the cold and hot plates are within the specified range. The heat flow meter must be calibrated before testing to ensure the accuracy of the measurement data.

[0151] Sound insulation performance test: refer to ISO 140-3 standard, using acoustic test equipment. The composite foam board is made into a sound insulation test piece with appropriate size, which is installed between the sound source chamber and the receiving chamber of the sound insulation test device. The sound source chamber emits white noise with a frequency range of 315-2000 Hz. The sound pressure level (dB) after passing through the test piece is measured by the acoustic sensor of the receiving chamber. Compared with the sound pressure level without the test piece, the sound insulation volume (dB) is calculated. The larger the sound insulation volume, the better the sound insulation performance. During the sound insulation performance test, the sealing performance of the sound insulation test device should be ensured to prevent external noise from interfering with the test results. The acoustic sensor should be calibrated before and after the test to ensure the accuracy of the sound pressure level measurement.

[0152] The results are shown in Table 1 below:

[0153] Table 1

[0154]

[0155]

[0156] Data analysis:

[0157] As can be seen from Table 1, the high bonding strength flame-retardant composite foam board prepared by the present application has higher bonding strength, higher flame retardancy, better heat insulation performance and sound insulation effect;

[0158] Reason for the difference in bond strength: In Examples 14-16, the modified epoxy resins were prepared through a two-step modification process. First, carboxyl-terminated nitrile butadiene rubber (CTBN) was reacted with bisphenol A epoxy resin. The carboxyl groups of the CTBN chemically bonded with the epoxy groups of the epoxy resin, introducing flexible segments that increased the epoxy resin's toughness and adhesion to various materials. The subsequent addition of styrene-butadiene rubber particles was uniformly dispersed through mechanical blending, further enhancing the system's flexibility and stress-dispersing properties. This composite modification enables the epoxy resin to better fuse with the outer skin, inner skin and foaming agent during the foaming and curing process, forming a tight chemical bond and physical entanglement network; compared with Example 3, no modified epoxy resin is added, and its epoxy resin system is relatively rigid. After foaming and curing, the interface bonding with the skin relies only on the limited adhesion of the epoxy resin itself, lacking the buffering and reinforcing effect of the flexible chain segment. When subjected to tensile external force, the stress concentration phenomenon at the interface is obvious, which easily leads to peeling, resulting in low bonding strength. Comparative Example 4 uses pre-modified epoxy resin, which lacks the step of further optimizing the structure of solid rubber particles. The flexibility and stress dispersion uniformity of the system are poor. It is not as good as the embodiment, so the bonding strength is at an intermediate level. Although it is worse than Comparative Example 3, it is not as good as Examples 14-16; Comparative Example 5 uses an equal amount of a mixture of terminal carboxyl nitrile rubber, bisphenol A epoxy resin and styrene butadiene rubber. Due to the lack of pre-reaction and fine blending process, the components cannot form an orderly network structure as in the embodiment, and the rubber phase may agglomerate, and cannot fully play the role of enhancing bonding, resulting in unsatisfactory bonding strength; Comparative Example 6 changes the ratio of bisphenol A epoxy resin to modified epoxy resin, destroying the originally optimized formula system, causing the overall performance to be unbalanced and the bonding strength to be affected. Although it is worse than Comparative Examples 3 and 5, it is not as good as the embodiment with a reasonable ratio.

[0159] Reasons for the difference in flame retardant performance: The modified epoxy resins in Examples 14-16, on the one hand, CTBN itself contains a certain amount of nitrogen elements, which can release inert gases such as nitrogen during the combustion process, dilute the concentration of combustible gases, and play a role in gas phase flame retardancy; on the other hand, the modification process optimizes the cross-linking structure of the epoxy resin, so that it forms a denser and more stable carbon layer at high temperature, blocking the transfer of heat and oxygen to the internal material, and inhibiting further development of combustion. Comparative Example 3 did not use modified epoxy resin. When the material was burning, the thermal stability of the epoxy resin was relatively poor, and it was easy to decompose to produce combustible small molecules. The formed carbon layer was loose and could not effectively block flames and heat, resulting in prolonged burning time, the appearance of dripping, and the flame retardant grade was reduced to V-1. Comparative Example 5 is similar to Comparative Example 3. Since the optimized modified epoxy resin system was not used, the flame retardant performance was poor and only reached V-1 level. Although the overall formula of Comparative Examples 4 and 6 has been adjusted, the basic flame retardant properties of the modified epoxy resin are still retained to a certain extent, so the V-0 level can be maintained. However, in some detailed indicators, such as the quality of the char layer after combustion, they may not be as good as Examples 14-16.

[0160] Reasons for the difference in thermal insulation performance: The higher content of modified epoxy resin in Example 16 plays a key role in the foaming process. Its optimized molecular structure makes the foamed pores more uniform, small and with a high closed-cell rate. Small and uniform pores reduce the path of heat conduction, because the heat conduction rate in gas is much lower than that in solid materials; the high closed-cell rate prevents the convection heat exchange of air. The air is enclosed in the pores and cannot form an effective convection cycle, thereby greatly reducing heat transfer. In contrast, Comparative Example 3 does not have the regulation of modified epoxy resin, and the foaming structure is relatively rough, the pore size is uneven and the closed-cell rate is low. Hot air can easily be convectively transferred through larger pores and connected pores, resulting in increased thermal conductivity and poor thermal insulation performance. Due to the adjustment of the formula, Comparative Examples 4-6 cannot accurately control the foaming process like Example 16. The pore structure is in an intermediate state, and the thermal insulation performance is also between the Example and Comparative Example 3.

[0161] Reason for the difference in sound insulation performance: The modified epoxy resin system in Example 16 improves the internal microstructure of the composite foam board. On the one hand, the uniform and fine pore structure is similar to that of a sound-absorbing sponge. After sound waves enter, they are repeatedly reflected and scattered within the pores, continuously consuming energy. On the other hand, the modified epoxy resin, which is rich in flexible segments, increases the material's damping properties. When sound waves cause the material to vibrate, the vibration energy is quickly converted into other forms such as heat and dissipated, reducing the transmission of sound waves. Comparative Example 3 lacks the optimization of the modified epoxy resin, and its pore structure is not conducive to sound absorption. The material has low damping, allowing sound waves to easily penetrate, resulting in low sound insulation. Comparative Examples 4-6 also have inferior sound insulation performance due to their less ideal structure than Example 16, and cannot achieve the high-efficiency sound insulation effect of Example 16.

[0162] In summary, the modified epoxy resin optimizes the microstructure, chemical bonding, material compatibility and other aspects of the composite foam board, so that Examples 14-16 show obvious advantages over Comparative Examples 3-6 in various performances, providing strong support for the high performance of high-bonding strength flame-retardant composite foam boards.

[0163] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Within the scope of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0164] The present application is intended to cover all such alternatives, modifications, and variations as fall within the broad scope of the appended claims. Accordingly, any and all such alternatives, modifications, equivalents, improvements and the like are intended to be encompassed by the present application.

Claims

1. A high bonding strength flame retardant composite foam board, characterized in that: The composite foam board comprises an outer skin, an epoxy foam core and an inner skin from top to bottom; The epoxy foam core is an epoxy foam-based composite material; The epoxy foam-based composite material is prepared from the following raw materials: epoxy resin base material, curing agent, foaming agent, flame retardant, surfactant and toughening agent; The epoxy resin base material is obtained by mixing bisphenol A epoxy resin and modified epoxy resin; The modified epoxy resin is a rubber-modified bisphenol A epoxy resin; The flame retardant is aluminum hydroxide; The surfactant is silicone oil; The toughening agent is nitrile rubber; The preparation process of the modified epoxy resin is as follows: Step A1. A bisphenol A epoxy resin is placed in a three-necked flask equipped with a stirrer and a thermometer and preheated at 80°C for 10-15 minutes to reduce the viscosity of the bisphenol A epoxy resin and facilitate subsequent mixing. Carboxyl-terminated nitrile rubber is then added to the bisphenol A epoxy resin and stirred at 90°C for 3 hours at a stirring speed of 300-500 rpm to allow the carboxyl groups in the carboxyl-terminated nitrile rubber to fully react with the epoxy groups in the epoxy resin to obtain a pre-modified epoxy resin. Step A2. The styrene-butadiene rubber particles are added to the pre-modified epoxy resin and mixed at room temperature using a high-speed stirrer at a stirring speed of 1000-1200 rpm for 30-40 min to ensure that the solid rubber particles are evenly dispersed in the modified epoxy resin to obtain a modified epoxy resin; The mass ratio of bisphenol A epoxy resin to modified epoxy resin in the epoxy resin base material is 100-105:11.5-15.

2. The high-bonding-strength flame-retardant composite foam board according to claim 1, characterized in that: The mass ratio of the epoxy resin base material, the curing agent, the foaming agent, the flame retardant, the surfactant and the toughening agent in the epoxy foam-based composite material is 125-128:13-15:11-14:48-52:1-1.5:10-10.

5.

3. The high-bonding-strength flame-retardant composite foam board according to claim 2, characterized in that: The curing agent is diethylenetriamine; The foaming agent is pentane.

4. The high-bonding-strength flame-retardant composite foam board according to claim 1, characterized in that: The thickness of the outer skin is 0.15-10 mm, and the outer skin is any one of aluminum alloy, steel plate, PC, ABS, PA66, PVC, glass fiber, glass fiber reinforced plastic and carbon fiber.

5. The high bonding strength flame retardant composite foam board according to claim 1, characterized in that: The thickness of the inner skin is 0.15-10 mm, and the inner skin is any one of aluminum alloy, steel plate, PC, ABS, PA66, PVC, glass fiber, glass fiber reinforced plastic and carbon fiber; The thickness of the epoxy foam core is 3-100 mm.

6. The high-bonding-strength flame-retardant composite foam board according to claim 1, characterized in that: The mass ratio of the carboxyl-terminated nitrile rubber to the bisphenol A epoxy resin in step A1 is 12-16:90-110.

7. The high-bonding-strength flame-retardant composite foam board according to claim 1, characterized in that: The mass ratio of the styrene-butadiene rubber particles to the pre-modified epoxy resin in step A2 is 10-13:110-120.

8. The method for preparing a high-bonding-strength flame-retardant composite foam board according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step S1. Preheat the bisphenol A epoxy resin and the modified epoxy resin at 35-40°C, add the flame retardant, and stir at 45-50°C for 15 minutes at a stirring speed of 500-800 rpm. Then, add the foaming agent and stir at 800-1000 rpm for 8 minutes to obtain a mixture 1; Step S2. Adding a surfactant and a toughening agent to the mixture 1, stirring at 400-700 rpm for 12 min, and finally adding a curing agent, stirring at 800-1200 rpm for 3 min to obtain an epoxy foam-based composite material; Step S3. Place the inner and outer skins of the same height vertically against the mold wall in the mold and secure them. The mold height should be consistent with the inner and outer skins, and the bottom of the mold should be in close contact with the inner and outer skins. Step S4. Inject the epoxy foam-based composite material into a mold, place it at room temperature for 6-24 hours, then place it at 80-120°C for 2-3 hours, and demold it after foaming and curing to obtain a high-bonding-strength flame-retardant composite foam board.

Citation Information

Patent Citations

  • Method for manufacturing phenol-formaldehyde-foam-filled honeycomb core reinforced advanced compound material

    CN102198744A

  • Honeycomb sandwich panel

    CN103291035A

  • Honeycomb aluminum-epoxy resin composite sandwich plate and preparation method thereof

    CN104760340A

  • Epoxy resin adhesive and preparation method and applications thereof

    CN102977830A

  • Stiffener film substrate composition, stiffener film substrate as well as stiffener film and steel plate composite material

    CN103509506A